Prospecting indigenous Bt isolates for bioinsecticidal efficiency against soil-borne white grub, Holotrichia serrata (F.) (Coleoptera: Scarabaeidae) - Manoj, M.; Tamilvendan, K.; Chavan, Mohan; Selvakumar, G.; Nagaraju, K.; Manjunatha, C. (Journal of Asia-Pacific entomology, 2025)
[Display omitted] •Indigenous Bt isolates were screened for bioinsecticidal activity against H. serrata.•Bt isolate UASB Bt11 showed the highest toxicity, with 100 % I-instar mortality within one day after treatment (DAT). II and III instar mortality rates ranged from 0 to 66.70 % at 15 DAT and 0 and 33.3 % at 30 DAT, respectively.•LC50 values confirmed high virulence of UASB Bt11 against all grub instars.•Study supports Bt-based biopesticide development for white grub management. White grubs (Holotrichia serrata) are among the most destructive insect pests in Indian agriculture, severely affecting a wide range of crops. Despite the availability of various insecticides, managing these pests remains challenging. This study aimed at exploring efficient local Bacillus thuringiensis (Bt) strains that exhibited insecticidal activity against white grubs. Morphological characterization revealed that isolates were rod-shaped and formed endospores. 16S rRNA-based molecular characterization confirmed that the strains shared identity with Bt. Toxicity evaluation of the Bt strains against different instars of grubs showed mortality rates ranging from 0 to 100 %. Notably, 18 out of 24 strains caused 100 % mortality in first-instar grubs within one day after treatment (DAT). Further testing of these isolates against second and third-instar grubs revealed mortality rates ranging from 0 to 66.70 % (15 DAT) and 0 to 33.3 % (30 DAT), respectively. The LC50 values of these strains ranged from 149.95 to 275.46 µg/mL for first, 161.54 to 294.24 µg/mL for second, and 254.64 to 415.60 µg/mL for third instar grubs at 120 h post-treatment. The isolate UASB Bt11 exhibited best biocontrol ability against all the stages of the grub. The results also indicated that first-instar grubs are the most susceptible to Bt, with sensitivity declining in later stages. This study demonstrates the biopesticidal potential of local Bt isolates or their crystal toxin genes against H. serrata for development of insect-resistant crops like sugarcane.